Analysis of Language Attitude and Language Preservation in Javanese Language.: A Case Study of Javanese Speaker in Madiun, East Java - Sonya Ayu Kumala (e-LinguaTera, 2021)
People socialize trough language. Language uses as media of communication and fulfils formal and informal roles in society. In communicating, people have their preference in using certain language for certain roles. Speaker preferences represent their language attitude toward those languages. Speaker attitude of language will strongly affect the preservation of language. In East Java, the regional language is Javanese language. However, people tend to use Indonesia language or Javanese language as their lingua franca in this modern era. This phenomenon encourages one language become dominant or minor. This paper focuses on the attitude of Javanese speaker among participant. The writer chooses participant from Javanese speaker in Madiun, East Java. Participants are chosen in consideration of aspects native speaker and distribution of Javanese language in Java. The domain of language usage and variety of attitudes are used to measure the attitude of language speaker. Besides investigating the language attitude of the participant, in this article, the writer also analyses the language preservation of the participant. The result shows that the participant perform positive attitude toward Javanese language. Therefore, the language preservation that has done by the participant is in the intermediate level. This article is, therefore, only a case study of language attitude, particularly to see how the attitude of native speaker of Javanese language can be problematic in the modern era